Efektivitas Penggunaan Media Komunikasi Facebook dan Instagram Terhadap Kinerja Pemerintah Desa Suka Karya Kecamatan Tungkal Ilir Kabupaten Banyuasin - Firmansyah Firmansyah; Fifi Hasmawati; Muhammad Randicha Hamandia (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This research is based on efforts to utilize the internet through social media Facebook and Instagram in communication, because the performance of the village government experienced a decline due to late access to information data reaching village officials. This research aims to determine the effectiveness of the use of Facebook and Instagram communication media on the performance of the Suka Karya Village Government, Tungkal Ilir District, Banyuasin Regency. The research methodology uses quantitative. Data collection techniques include observation, questionnaires and documentation, then data analysis techniques through validity testing, reliability testing, normality testing and hypothesis testing. The results of the research are the obtained hypothesis test value, f test, F value 6,284 > 2.69 F table, significant value 0.02 < 0.05, so there is a simultaneous influence between Facebook and Instagram Communication variables (X) on Performance (Y). then using the t test the sig value for the influence of Suka Karya Village, Tungkal Ilir District, Banyuasin Regency, so it can be said that Hypothesis (H1) is accepted.